Telomere length, family history, and paternal age in schizophrenia - Malaspina, Dolores (BlackWell Publishing Ltd, 2014)
Leukocyte telomere length (LTL) is longer in association with advanced paternal age, but this association has not been examined along with family history (FH) in schizophrenia. LTL was measured by PCR and compared across cases and controls as part of a study to examine the characteristics of paternal age related schizophrenia. The 53 schizophrenia cases had similar mean LTL as 20 controls, although cases were significantly older than controls and overwhelmingly smoked cigarettes. Multivariate analyses showed that a FH of schizophrenia was associated with longer LTL in both male and female cases. Later paternal age was also related to longer LTL in male cases, but with shorter LTL in female cases. Male cases with older fathers and a FH had the longest LTL. The genetic architecture associated with a familial risk for schizophrenia may include pathways that lengthen LTL. Paternal aging conferred an additional increase in LTL lengthening in male cases, but reduced LTL in female cases. The gender difference in LTL for paternal aging is consistent with the severe illness features reported for female cases with older fathers and could implicate epigenetic alterations in the paternal X chromosomal region with advanced paternal age in association with the risk for schizophrenia.